2020
DOI: 10.1080/10717544.2019.1709919
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced cytotoxicity of a redox-sensitive hyaluronic acid-based nanomedicine toward different oncocytes via various internalization mechanisms

Abstract: Shen (2020) Enhanced cytotoxicity of a redox-sensitive hyaluronic acid-based nanomedicine toward different oncocytes via various internalization mechanisms, Drug Delivery, 27:1, 128-136, ABSTRACTReceptor-mediated active targeting and tumor microenvironment responsive systems from polymeric micelles have been studied for rapid cellular internalization and triggered drug release. Previously we have constructed redox-responsive polymeric micelles composed of vitamin E succinate conjugated hyaluronic acid (HA-ss-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…2.4.3 Redox sensitivity of HA-SeSe-COOH/siR-93C@PAMAM HA-SeSe-COOH/siR-93C@PAMAM were treated with L-Glutathione (GSH concentration 10 nM or 20 µM) [18,31,32], H 2 O 2 (7.0 µmol/L or 1.0 mmol/L) [33][34][35][36][37], and normal saline, respectively. The particle size and the polydispersity index of ve groups were measured every 30 min to value the redox sensitivity of HA-SeSe-COOH/siR-93C@PAMAM.…”
Section: Gel Electrophoresis Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…2.4.3 Redox sensitivity of HA-SeSe-COOH/siR-93C@PAMAM HA-SeSe-COOH/siR-93C@PAMAM were treated with L-Glutathione (GSH concentration 10 nM or 20 µM) [18,31,32], H 2 O 2 (7.0 µmol/L or 1.0 mmol/L) [33][34][35][36][37], and normal saline, respectively. The particle size and the polydispersity index of ve groups were measured every 30 min to value the redox sensitivity of HA-SeSe-COOH/siR-93C@PAMAM.…”
Section: Gel Electrophoresis Assaymentioning
confidence: 99%
“…Stimuli-triggered dis-shielding strategies have attracted enormous interest and boosted intense studies to improve the safety of PAMAM, redox-triggered dis-shielding is one of them, which is highly valued in cancer treatment. Compared with normal cells, most tumor cells exhibit higher levels of reactive oxygen species (ROS) and glutathione (GSH), it has been reported that the concentration of GSH in tumor tissues was at least 4-fold higher than that in normal tissues [17,18]. This unique redox environment of tumor allows the breakage of redox sensitive bonds to release loaded cargoes, for example disul de bonds [9,19,20].…”
Section: Introductionmentioning
confidence: 99%